Acute acalculous cholecystitis and gall bladder perforation induced by Salmonella enterica serovar typhi - Khatri, N. S.; Koirala, S.; Arjyal, A.; Maskey, P.; Poudel, S.; Karkey, A.; Baker, S.; Shilpakar, O.; Shrestha, K.; Basnyat, B. (Journal of Institute of Medicine Nepal, 2010)
Salmonella Typhi is a causative agent of enteric fever, which is an ongoing public health problem in urban areas of the Kathmandu valley in Nepal. It is estimated that approximately 5 % of people in an endemic enteric fever area may asymptomatically carry Salmonella Typhi in the gall bladder. Here we describe a rare clinical manifestation of chronic Salmonella carriage. A 40 year old male resident of Kathmandu underwent an emergency cholecystectomy for acute cholecystitis and gall bladder perforation. No stone was identified but Salmonella Typhi was cultured from the gall bladder. Key Words: Acalculous cholecystitis, perforation, Salmonella Typhi. DOI: 10.3126/joim.v31i3.3002 Journal of Institute of Medicine, December, 2009; 31(3)63-65